Purification and properties of Halobacterium cutirubrum L-alanine dehydrogenase. - Kim, Edward K. (University of Ottawa (Canada), 1978)
The purpose of this work was to purify and study an extreme halophile enzyme unrelated to nucleic acid metabolism in order to compare its properties with those of H. cutirubrum polynucleotide phosphorylase, DNA-dependent and RNA-dependent RNA polymerase, and alkaline phosphatase. The last four enzymes were found to be unusually small by Fitt and his collaborators and it was desirable to examine in detail a protein unrelated to nucleic acid metabolism. L-alanine dehydrogenase was chosen because its assay is straight-forward and preliminary studies showed that it was highly active in crude extracts of H. cutirubrum. The enzyme was purified approximately 100-fold by a simple procedure and found to have a molecular weight of 72,500, about one third that of the two well-studied alanine dehydrogenase from non-halophiles. It catalyses the oxidative deamination of L-alanine and L-alpha-aminobutyric acid to pyruvate and alpha-ketobutyric acid, respectively, and the reductive amination of pyruvate and several other alpha-keto acids. An unusual feature is the absolute requirement of the enzyme for K + for catalysis of the oxidative deamination reaction; Na+ , Li+, Cs+, and NH+4 are unable to replace K+. In contrast, in the reductive amination reaction the enzyme is fully active in the presence of high concentrations of K+, Na+ or NH+4 and partially active with Cs+ or Li+ - NH+4 , is, of course, an essential substrate in this reaction as well. As in the case of most other halophilic enzymes, the L-alanine dehydrogenase requires a high salt concentration absolutely for stability and activity. The activity of the enzyme increases with temperature up to 70°C, but the protein itself is not thermostable.
Keywords: Chemistry, Biochemistry.